A Training on Multi-Trait Selection Index and Random Genetic Analysis in Wolayta Sodo, Ethiopia - Getachew, Tesfaye; Belay, Berhanu; Haile, Aynalem (International Center for Agricultural Research in the Dry Areas, 2023)
A two-day advanced training session on Multi-Trait Selection Index, and Random Genetic Analysis was conducted in Wolaita Sodo city, in Ethiopia. The training specifically targeted researchers involved in implementing sheep and goat CBBPs. Pedigree and performance data collection, genetic evaluation, selection and optimization of the breeding program are integral components of sheep and goat community-based breeding programs in Ethiopia. CBBP has been implemented in Ethiopia since 2009, and substantial genetic progress has been attained for the traits considered in the program.